Front Cover. Issue 4 (13th March 2021) - Zhang, Zhixin; Kass, Jamie M.; Mammola, Stefano; Koizumi, Itsuro; Li, Xuecao; Tanaka, Kazunori; Ikeda, Kousuke; Suzuki, Toru; Yokota, Masashi; Usio, Nisikawa
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13225 "Lineage‐level distribution models lead to more realistic climate change predictions for a threatened crayfi sh" by Zhixin Zhang et al. The photo (taken in 2009) shows an eastern lineage Japanese crayfi sh (Cambaroides japonicus) in a small woodland stream in Hokkaido, Japan. Photo credit: Nisikawa Usio.